2021
DOI: 10.1016/j.jbc.2021.100797
|View full text |Cite
|
Sign up to set email alerts
|

Structures and kinetics of Thermotoga maritima MetY reveal new insights into the predominant sulfurylation enzyme of bacterial methionine biosynthesis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 75 publications
1
40
0
Order By: Relevance
“…For clarity, only the active site residues are shown. An O-acetyl-homoserine derivative reaction intermediate captured within the MetY structure (Brewster et al, 2021) is shown in semi-transparent spheres. Residue labeling corresponds to the Yll058w sequence.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For clarity, only the active site residues are shown. An O-acetyl-homoserine derivative reaction intermediate captured within the MetY structure (Brewster et al, 2021) is shown in semi-transparent spheres. Residue labeling corresponds to the Yll058w sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence similarity and evolutionary relationship of Yll058w to enzymes involved in sulfur metabolism led us to examine its predicted structure. To do so, we utilized the crystal structure of MetY ( Figure S7A ), a bacterial O -acetylhomoserine aminocarboxypropyltransferase that catalyzes the homocysteine biosynthesis from O -acetylhomoserine and bisulfide (Brewster et al ., 2021), as well as the predicted structures of Met15 and Yll058w generated by AlphaFold2 (Jumper et al, 2021). The MetY crystal structure captured a reaction intermediate, allowing for a precise determination of active site residues.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations